Rigidity-Tunable Materials for Soft Engineering Systems - Roh, Yeonwook; Lim, Daseul; Kang, Minji; Cho, Junggwang; Han, Seungyong; Ko, Seung Hwan (Advanced Engineering Materials, 2024)
Engineering systems that leverage the flexibility and softness of soft materials have been fostering revolutionary progress and broad interest across various applications. The inherently flexible mechanical properties of these materials lay the groundwork for engineering systems that can adapt comparably to biological organisms, enabling them to adjust to unpredictable environments effectively. However, alongside the positive benefits of softness, these systems face challenges such as low durability, continuous energy demands, and compromised task performance due to the inherently low stiffness of soft materials. These limitations pose significant obstacles to the practical impact of soft engineering systems in the real world beyond innovative concepts. This review presents a strategy that employs materials with variable stiffness to balance adaptability advantages with the challenge of low rigidity. The developments are summarized in materials capable of stiffness modulation alongside their applications in electronics, robotics, and biomedical fields. This focus on stiffness modulation at the material unit level is a critical step toward enabling the practical application of soft engineering systems in real-world scenarios.
Keywords: Engineering systems; Rigid to soft transition; Soft engineering; Soft robot; Soft-transition; Softer materials; Stiffness modulation; Tunable materials; Tunable rigidity; Tunables; rigid to soft transition; soft materials; soft robots; tunable rigidity